Enhancing public communication effectiveness through information systems capabilities and organizational maturity: Evidence from a utility service project in Indonesia - Maria, Yulita; Riyadi, Slamet; Cempena, Ida Bagus (Edelweiss Applied Science and Technology, 2025)
Successful public communication in utility companies increasingly depends on the alignment of information systems capability with organizational maturity. This research examines the influence of ICT capability, digital literacy, and business process standardization on communication effectiveness, with information governance maturity acting as a moderator. Using a quantitative explanatory approach, data were collected from 69 PLN UP3 Berau employees in Indonesia and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that ICT capability and electronic skills improve communication effectiveness primarily when supported by standardized processes and mature governance. Business process standardization emerged as the most significant predictor, highlighting the importance of formalized information flows and process clarity in enhancing communicative performance. Additionally, information governance maturity strengthens the effects of processes and skills, serving as an institutional enabler of transparency and coordination. This study advances the literature on information systems and e-government by proposing a governance-centered communication model that integrates technological, human, and procedural dimensions, offering strategic insights for policymakers and utility managers to boost citizen engagement and digital communication performance.